Cross-cultural differences in obsessive-compulsive symptom dimensions across young adults in Mexico and USA. Issue 5 (27th May 2020) - Berman, Noah Chase; Gallegos-Guajardo, Julia; Reuman, Lillian; Ramirez, Manuel; Valdez, Gladys; Abramowitz, Jonathan S.
ABSTRACT: Despite cross-cultural differences in obsessive-compulsive disorder (OCD) symptomology, little work has been extended in those in Mexico. To bridge this gap, the current study administered standardised and culturally-validated measures of OCD and a critical cultural construct – spirituality – to young adults in Mexico ( n = 430) and the USA ( n = 194). Linear regression analyses indicated that individuals in Mexico reported significantly greater scores on all obsessive-compulsive (OC) dimensions, when compared to those in the USA. The association between nationality and all OC symptom dimensions (except responsibility for harm) depended upon degree of spirituality; as spirituality increased, OCD severity decreased in the Mexican sample and increased in the USA sample. The potentially protective role of spirituality in Mexican participants may be explained by the collectivist culture, which can inform culturally-tailored interventions. Our study was limited by our analogue sample and cross-sectional design. Future researchers should collect longitudinal data and employ random sampling methods.